The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/deci.12329
|View full text |Cite
|
Sign up to set email alerts
|

Prediction‐Oriented Model Selection in Partial Least Squares Path Modeling

Abstract: Partial least squares path modeling (PLS-PM) has become popular in various disciplines to model structural relationships among latent variables measured by manifest variables. To fully benefit from the predictive capabilities of PLS-PM, researchers must understand the efficacy of predictive metrics used. In this research, we compare the performance of standard PLS-PM criteria and model selection criteria derived from Information Theory, in terms of selecting the best predictive model among a cohort of competin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
128
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 149 publications
(151 citation statements)
references
References 93 publications
1
128
0
Order By: Relevance
“…A potential objection regarding the use of PLS-SEM compared with factor-based SEM could be that the method does not offer model modification indices to readily address potential problems of model misspecification as caused by, for example, omitted variables. However, recent research has introduced procedures for comparing PLS path models in terms of model fit and predictive power (Liengaard et al, 2020; Sharma et al, 2019, 2020). While these procedures do not provide a stand-alone assessment of a model, they allow contrasting different model configurations that vary, for example, the position of a moderator in a conditional process model.…”
Section: Resultsmentioning
confidence: 99%
“…A potential objection regarding the use of PLS-SEM compared with factor-based SEM could be that the method does not offer model modification indices to readily address potential problems of model misspecification as caused by, for example, omitted variables. However, recent research has introduced procedures for comparing PLS path models in terms of model fit and predictive power (Liengaard et al, 2020; Sharma et al, 2019, 2020). While these procedures do not provide a stand-alone assessment of a model, they allow contrasting different model configurations that vary, for example, the position of a moderator in a conditional process model.…”
Section: Resultsmentioning
confidence: 99%
“…Shmueli et al (2018) use this model and a subset of the data to illustrate Shmueli et al's (2016) PLSpredict procedure. However, Shmueli et al's (2018) presentation draws on a more complex variant of the model by illustrating PLS-SEM's predictive capabilities, which favor the use of a more complex model (Sharma et al, 2019b). 3.…”
Section: Authors' Notementioning
confidence: 99%
“…In addition, the many controversial debates about the method's merits and limitations, witnessed in different research fields (Khan et al, 2019), have increased awareness of it (Petter, 2018). As part of these debates, researchers identified blind spots in PLS-SEM, which methodologists were quick to fill by developing methodological improvements (Franke and Sarstedt, 2019;Henseler et al, 2015;Sharma et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…In our case we found that small values are achieved in the effect size (Table 9). Finally, to test the predictive power of the model, the PLSpredict procedure (Sharma et al, 2018) was used, obtaining the results presented in Table 10. It is evident that, in all cases, the Q2predict values are above zero and in half of the indicators higher RMSE values are obtained using PLS versus LM, which indicates that the model has an medium predictive power (Shmueli et al, 2019;.…”
Section: Figure 3 Results Of the Structural Modelmentioning
confidence: 99%